Assessment of body composition by whole-body densitometry: what radiologists should know - Chaves,Lucas Gabriel Cruz de Menezes (2022)
Abstract The analysis of body composition is a fundamental part of a nutritional status assessment, and the use of diagnostic imaging methods has been increasingly required for an adequate characterization of the lean body mass and fat mass. Body composition measurements are useful in evaluating the effectiveness of nutritional interventions and monitoring changes associated with aging and chronic diseases. Whole-body densitometry using dual-energy X-ray absorptiometry (DEXA) is one of the most widely used methods in clinical practice, allowing highly accurate assessment of the bone mineral content, lean body mass, and fat mass. Although a DEXA examination provides a lot of information, there is still no universal standardization of the parameters to be included in radiology reports. The aim of this study was to review the most relevant information for assessing body composition by whole-body densitometry.